Una fonte per la storia della moda italiana: l’Archivio Rosa Genoni - Soldi, Manuela (ZoneModa Journal, 2018)
The paper would give information about a first description of Rosa Genoni and Alfredo Podreider (Genoni’s husband) archive carried out between 2015 and 2016 under the supervision of Lombardy Soprintendenza archivistica (regional archive authority) and the State Archive of Milan by Manuela Soldi, who studied Genoni during her doctoral research. In Milan between XIX° and XX° century, Rosa Genoni was a teacher and a tailor famous for her proposal of Italian Fashion during the Milan International Exhibition in 1906, also known for her socialist militancy and pacifist ideas. The work on the archive highlights the bonds between the various fields of Genoni’s activities, showing the complex remaining of a life and a family. The archive is not only a source for fashion studies but also for other branch of knowledge, which needs a comprehensive description to allow its conservation and investigation.